ANALISIS KEPUASAN KERJA PERAWAT RUMAH SAKIT PRIMA PEKANBARU RIAU - Deswarta Deswarta (Jurnal Ekonomi Manajemen Bisnis Syariah dan Teknologi, 2022)
The main purpose of this study was to find out and analyze job satisfaction and expectations of nurses at Prima Pekanbaru Hospital. This research was conducted at Prima Hospital which is located at Jalan Bima No. 1 on Nangka Ujung/Tuanku Tambusai Street, Pekanbaru. The population in this study were 206 people. however, as the sample in this study, there were 67 nurses using the slovin formula. then the analysis used in this research is descriptive qualitative analysis method using purposive sampling method. The research results show that. overall respondents' responses to the variable job satisfaction are in the good category. The hospital should always further increase job satisfaction for nurses so that they are more enthusiastic about working.